Reguły Nelsona Mandeli - Mrozek, Kamila (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The publication is entirely devoted to the UN Standard Minimum Rules for the Treatment of Prisoners from 2015. However, due to their large size, this work focuses solely on the comparison of the presently valid rules with those from the UN Standard Minimum Rules for the Treatment of Prisoners from 2015 accepted in Geneva in 1955. The changes have been discussed one by one. The work also explains the evaluation of the legal status of the UN Nelson Mandela Rules because as a recommendation they lack the binding legal provisions. Nevertheless, they should become not only the generally accepted standard of prisoner protection against maltreatment, but even more so the model of penitentiary influence on convicts.
Keywords: Reguły Mandeli; skazany; usługi medyczne; kara więzienia; prawo międzynarodowe